Electromigration Techniques in the Analysis of Selected Cosmetic Ingredients: A Review - Joanna Kończyk; Magdalena Myga-Nowak; Rajmund Michalski; Katarzyna Janoszka (Molecules)
The cosmetics industry is one of the fastest-growing sectors worldwide. The dynamic evolution of this industry results in an increasingly diverse range of products containing various active ingredients. Ensuring the quality of these products is crucial for consumer safety, necessitating the use of advanced analytical methods and adherence to legal regulations. Electrophoretic techniques, particularly capillary electrophoresis and micellar electrokinetic chromatography, facilitate the rapid and precise separation and identification of cosmetic ingredients. A well-chosen technique and optimized analytical conditions ensure high sensitivity, repeatability, and resolution, achieving detection limits that meet legal requirements. Although electromigration techniques are less common in routine laboratory analyses compared to liquid chromatography, they show potential for broader application in analyzing various substances found in cosmetics. This study reviews the possibilities of applying different electrophoretic techniques to analyze selected cosmetic ingredients serving various functions, including preservatives, dyes, exfoliating agents, UV filters, and also contaminants, while considering sample preparation methods, equipment used, and analysis conditions. The compiled data indicate that capillary electrophoresis, when compared to high-performance liquid chromatography and ion chromatography, shows comparable or superior sensitivity and repeatability, with detection limits adequate to meet regulatory standards.